KARAKTERISTIK KONDISI KESEHATAN PADA PASIEN KORBAN TINDAK PIDANA PERDAGANGAN ORANG: TINJAUAN LITERATUR SISTEMATIS - Gizela, Beta Ahlam; Puspitasari, Kintan (Jurnal Forensik dan Medikolegal Indonesia, 2023)
Background: Human trafficking is a crime that degrades human dignity, involving hundreds or even thousands of victims per year both on a global and local scale. In the human trafficking, various types of violence often occur. It is important to identify that the patient is a victim of human trafficking when a doctor encounter a patient due to sexual violence. Doctor must pay more attention to collect evidence through anamnesis, physical examination, and advance examination. Thus, the next strategy to help victims of human trafficking can be carried out. Aim: To identify the characteristics of physical, mental, and sexual health conditions in patients victims of TPPO as well as medical measures taken. Method: This is a systematic literature review of the literature obtained from four databases: PubMed, Google Scholar, Sage Journal, and Semantic Scholar. A literature search using the SPIDER method is initial screening and screening before downloading. Selected literatures then put for further selection with criteria of inclusion and exclusion to obtain eligible literature. The next step is ecstraction by conducting a critical review using a checklist according to the design of literature research. Result: Five literatures are eligibile with 2 literature conduct medical examinations, 4 literature discussing physical health issues, 3 literature discussing reproductive health issues, and 4 literature discussing mental health issues. Some of the literatures show the most common physical health problems are tired, memory impairment, and headaches or dizziness. Sexual health problems are sexually transmitted infections, urination pain in women and the risk of pregnancy. Mental health problems are PTSD, anxiety, and depression, desire and even suicide attempts, substance or alcohol use. Conclusion: Victims of human trafficking (men, women, and children) experience physical, sexual, and mental health problems.